The Effects of 17 Weeks of Ballet Training on the Autonomic Modulation, Hormonal and General Biochemical Profile of Female Adolescents - Da Silva, Carla Cristiane; Goldberg, Tamara Beres Lederer [UNESP]; Soares-Caldeira, Lúcio Flávio; Oliveira, Ricardo Dos Santos; De Paula Ramos, Solange; Nakamura, Fábio Yuzo (De Gruyter, 2015)
This study aimed to examine the alterations in physiological and biochemical markers, after 17 weeks of ballet training in high level ballet dancers. Twenty four female ballet dancers from 12 to 15 years old took part in the study. The study followed 17 weeks of ballet training and analyzed changes in body composition, the autonomic nervous system and biochemical variables before and after (post) training. The internal training load was obtained using the session rating of perceived exertion (session-RPE) method, calculated as the mean weekly session-RPE, monotony and strain. After 17 weeks of training there were significant increases in body mass, height, lean body mass, total protein, urea, hemoglobin concentration, testosterone and thyroxine. During this period, decreases in relative body fat, uric acid, red blood cells, C-reactive protein, and ferritin were also found. After the training period, the autonomic modulation demonstrated significant positive alterations, such as increases in parasympathetic related indices. Based on the results obtained we concluded that ballet training led to improvements in body composition and autonomic modulation. In general hematological and biochemical variables demonstrated that the training did not have adverse effects on the health state of the adolescents.
Keywords: autonomic nervous system; ballet training; body composition; youth dancers